Study Of Deformation And Crack Propagation On Component During Reflow Soldering Process - Raja Gobal, Hehgeraj (Universiti Sains Malaysia, 2022)
A typical element found in electronic assemblies and devices is the multi-layered ceramic capacitor (MLCC). However, MLCC mechanical defects such as voiding, cracking, and delamination would significantly reduce the device's usefulness, dependability, and longevity. This mechanical defect is one of the significant factors that will develop in the surface mount of the multi-layered ceramic capacitor, especially the layer between the two different materials that are mounted together. Therefore, the purpose of this study is to study the crack propagation that will be found in the boundary of the copper and copper-epoxy layers of the multi-layered ceramic capacitor during the reflow soldering process. The numerical simulation method for the thermal reflow process of the MLCC model and the crack propagation from the initial micro voids due to the high moisture contamination on that layer was approached. Besides, the temperature flow and the moisture contamination on the copper and copper-epoxy layers were examined during the simulation for the causes of the crack propagation on the MLCC. From the results of the simulation conducted, the crack propagation in between the copper and copper-epoxy layers was caused by the thermal mismatch and propagation growth of micro voids during the reflow soldering process. As a result of the high pressure of vapour absorbed in the gap between the copper and copper-epoxy layer, it will have a greater capacity to absorb moisture and cause crack delamination, resulting in the higher temperatures required to commence the crack at 270 °C during the reflow process. At 284.2 (mg/mm3), the concentration is at its highest. Because of this, a multi-layered ceramic capacitor results in a 0.077218 mm deformation between copper and copper-epoxy. Higher vicinity stress, mode I stress intensity factor, and crack elongation rate would result from this greater void. The main reason for the temperature reflows that is related to the fracture propagation problems in capacitors has been identified, and workable solutions have thus been suggested. This would help the end-users by enhancing the performance and dependability of the electronic equipment, as well as minimizing the additional manufacturing costs and lead times required in locating and resolving the problems.